Environmental effect of co-firing and magnetic field on wood pellets combustion - Suzdalenko, Vera; Gedrovics, Martins (Journal of Environmental Engineering and Landscape Management, 2014)
The aim of the recent research is to provide stable, controllable and effective wood pellets combustion with minimum emissions. Two possibilities were chosen, investigated and analysed: wood pellets co-firing with propane-butane mixture and the use of a permanent magnet. The special pilot device was constructed in the laboratory of Heat and Mass Transfer in Institute of Physics. Two types of experiments were conducted: combustion with propane-butane supply (0.9 kW up to 1.27 kW) of wood pellets with different moisture content (W = 8%, 15%, 20% and 25%); combustion of wood pellets with applied magnetic field by using the permanent magnet, an propane-butane supply also was used. The main conclusion of the research is that co-firing and magnetic field can be used as an instrument to provide more effective burnout of volatiles and cleaner heat production.First published online: 19 Mar 2014